A Potential Weapon: Small Extracellular Vesicles from Mesenchymal Stem Cells Can Treat Chronic Non-Healing Wounds - Qian Wei; Xi Liu; Jian-Long Su; Ya-Xi Wang; Zi-Qiang Chu; Kui Ma; Qi-Lin Huang; Hai-Hong Li; Xiao-Bing Fu; Cui-Ping Zhang (Innovations in Biological Science Vol. 9, 2024)
The present study described the characteristics of MSC-sEVs and discussed their therapeutic potential in chronic wound treatment. Additionally, the study also provided an overview of the application avenues of MSC-sEVs in wound treatment. Chronic non-healing wounds have posed a severe threat to patients mentally and physically. Dysregulation of behavior in the surviving cells at the sites of wounds is known to be the key factor that destroys the healing process and prevents wound healing. Therefore, the mainstay of treating chronic non-healing wounds is controlling and reestablishing normal cellular function. In recent years, the therapy with mesenchymal stem cells (MSCs) has become a promising option for chronic wound healing and the efficacy has increasingly been attributed to their exocrine functions. Small extracellular vesicles derived from MSCs (MSC-sEVs) are reported to benefit almost all stages of wound healing by regulating the cellular behavior to participate in the process of inflammatory response, angiogenesis, re-epithelization, and scarless healing. The study summarized strategies for large-scale production and engineering of MSC-sEVs. This review may possibly provide meaningful guidance for chronic wound treatment with MSC-sEVs. Further research is still imperative to unveil the advantages and disadvantages of the clinical application of MSC-sEVs on chronic nonhealing wounds. After the above issues are resolved, it is believed that MSC-sEV therapy is expected to be a potential and encouraging method for rapid and complete regeneration of chronic non-healing wounds.